2021
DOI: 10.1037/xlm0000977
|View full text |Cite
|
Sign up to set email alerts
|

Misinformed and unaware? Metacognition and the influence of inaccurate information.

Abstract: The current study investigated the role of metacognition with respect to the consequences of exposures to inaccurate information. Previous work has consistently demonstrated that exposures to inaccuracies can confuse people and even encourage reliance on the falsehoods. We specifically examined whether people are aware of their likelihood of being influenced by inaccurate information, and whether engaging in metacognitive reflection is effective at reducing this influence. In three experiments, participants re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 83 publications
(193 reference statements)
2
53
0
Order By: Relevance
“…Furthermore, the tendency to engage in analytic thinking predicts the ability to distinguish between true and false news content [18] and that reliance on emotion [78] and intuition [32] increases belief in fake news (see also; [78]). Relatedly, there is evidence that metacognitive promptsprobing questions that have people reflectincreases resistance to inaccurate information [121]. This work suggests that interventions aimed at getting people to slow down and reflect about the accuracy of what they see on social media may be effective in slowing the spread of misinformation.…”
Section: Promising Prospects For Fighting Misinformationmentioning
confidence: 83%
“…Furthermore, the tendency to engage in analytic thinking predicts the ability to distinguish between true and false news content [18] and that reliance on emotion [78] and intuition [32] increases belief in fake news (see also; [78]). Relatedly, there is evidence that metacognitive promptsprobing questions that have people reflectincreases resistance to inaccurate information [121]. This work suggests that interventions aimed at getting people to slow down and reflect about the accuracy of what they see on social media may be effective in slowing the spread of misinformation.…”
Section: Promising Prospects For Fighting Misinformationmentioning
confidence: 83%
“…For example, recent work has demonstrated the utility of metacognitive prompts for helping people calibrate their perceived and actual resistance to inaccurate information. Salovich and Rapp (2020) reported that while people are generally unaware of their susceptibility to inaccurate information, prompting them to consider recent use of inaccurate information outside of the lab setting increased awareness and reduced their reliance on false assertions. More direct instructions or suggestions to consider the consequences of one's confidence may encourage more effective judgments (Horry et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, survey experiments have shown that asking participants to explain how they know whether a headline is true or false before sharing it increases sharing discernment [105], and having participants rate accuracy at the time of encoding protects against familiarity effects [106]. Relatedly, metacognitive promptsprobing questions that make people reflectincreases resistance to inaccurate information [107].…”
Section: New Approaches For Fighting Misinformationmentioning
confidence: 99%